Utilizing the Banking System For Digital Waqf Behavioral Approach of Millennial Muslims - Anggareni, Erike; Nurmalia, Gustika; Ja'far, A. Kumedi (El-Usrah: Jurnal Hukum Keluarga, 2024)
The objective of this study is to analyze the influence of the digital sharia banking system on cash waqf among the millennial population in the Sumatran Island. This study is a quantitative research that focuses on the millennial generation in the Sumatran Island. The sample size for this study consists of 349 respondents. The data analysis approach employed is the Partial Least Squares (PLS) Test utilizing smart PLS software version 7.0. The findings indicate that Perceived Usefulness (PU) does not exert a substantial impact on the decision to waqf money. This implies that the level of benefits experienced by users of the digital sharia banking system does not have the ability to affect the decision to donate money through waqf. The perceived ease of use (PEU) positively and significantly influences the decision to waqf money. This implies that the higher the comfort felt by the millennial generation through the digital sharia banking system, the more likely they are to decide to waqf money. The sense of the surrounding environment, known as Subjective Norm (SN), has a positive and considerable influence on the decision to waqf money through the digital sharia system. Hubristic Pride (HP) does not exert a substantial influence on the inclination to donate money through the digital sharia system, indicating that the decision of the millennial generation to engage in this practice is not driven by hubris pride in the form of narcissism.